Total Endoscopic Transcanal Cartilage Myringoplasty: A Prospective Study - Shakya, Dipesh; KC, Arun; Nepal, Ajit; Tamang, Nirmala (International Archives of Otorhinolaryngology, 2019)
Introduction Middle ear surgeries, including myringoplasty, have increasingly utilized endoscopes as an adjunct to or as a replacement for the operative microscope.Objectives The objective of the present study was to evaluate the graft uptake rate and to evaluate the hearing results.Methods This is a prospective study. We have analyzed 139 patients who underwent surgery for chronic otitis media (COM) of the mucosal type. All of the surgeries were performed exclusively under total endoscopic transcanal approach using tragal cartilage as graft, underlay technique. We have evaluated the postoperative graft uptake and performed a hearing evaluation at 6 weeks, at 12 weeks, and at 6 months.Results During the study period, 139 patients were included, out of which 13 were lost to follow-up; therefore, only 126 patients were assessed. All of the cases were performed under total endoscopic approach. As for the surgical outcome at the postoperative otoscopy, 3 cases had initial uptake at 3 months and failed later; therefore, complete closure of the perforation was observed in 97.6% (n = 123) of the patients 6 months after the intervention.Four patients presented with preoperative anacusis; therefore, only 122 patients were included for hearing evaluation. The preoperative air conduction threshold (ACT) and airbone gap (ABG) were 43.34 ± 11.53 and 24.73 ± 7.89, respectively.Postoperatively, the ACT and ABG closure were 28.73 ± 15.75 and 11.91 ± 8.41, respectively. This difference was statistically significant (p < 0.001).Conclusion The endoscopic approach for myringoplasty offers excellent visualization; avoids postaural approach, enables a faster recovery, requires less hospital stay, with excellent graft closure rate and improved functional outcomes.
Keywords: cartilage; endoscope; myringoplasty